Resistance Test of Some Rice Varieties to Brown Planthopper (Nilaparvata lugens Stal) Bogor Population Using Honey: Uji Resistensi Beberapa Varietas Padi terhadap Wereng Batang Coklat (Nilaparvata lugens Stal) Populasi Bogor Menggunakan Metode Honeydew Test - Rinaldi, James; Sari, Widya Puspita; Darmadi, Dedi; Nelly, Novri (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2022)
Brown planthopper or BPH (Nilaparvata lugens Stal, Hemiptera: Delpachidae) is a significant pest that is a severe problem to rice plants in various places, including Bogor District, East Java Province. Resistance of several varieties of rice to BPH of Bogor Population has not been reported. One method to determine a variety's resistance is the honeydew test. This study aims to determine the resistance of several rice varieties to BPH of Bogor population. This study used six different varieties as treatments, and carried out in five replications. Those varieties were Pelita, Mapan, Situ Bagendit, Ciherang, Inpari-33, and IR-64. The observations were made on the area of honeydew spots produced by BPH after consuming sap of rice plant. This research showed that the Situ Bagendit variety was relatively resistant to BPH of Bogor population. The Mapan and Pelita varieties were quite susceptable, while Inpari-33, Ciherang, and IR-64 were moderate. The region of origin where BPH grows and the testing procedure can affect the resistance category of one variety.